The Ritual Bridge between Narrative and Performance in the Gospel of Mark - Paul D. Wheatley (Religions, 2023)
The abundance of ritual descriptions in the Gospel of Mark suggests a discourse about ritual between the narrator and early audiences of the Gospel. The prominence of the ritual of baptism at the beginning (Mark 1:9–11) and anointing at the end (16:1–8), and the recurrence of themes introduced in Jesus’s baptism at turning points in the Gospel (9:2–8; 10:38–39; 15:38–39) suggest broader ritual—and specifically baptismal—significance in the narrative. Recent changes helpfully differentiate narrative- and performance-critical interpretive approaches as text-oriented (narrative) and audience-oriented (performance), but these hermeneutical methods also work in concert. This article combines cognitive studies of narrative immersion with observations about the role of ritual in group identity formation and the impartation of religious traditions to analyze the narration of ritual acts in Mark. Giving attention to the use of internal focalization and description of bodily movements in ritual narrations, this article argues that depictions of rituals in Mark involve the audience in ways that deliver audience-oriented interpretations through text-oriented means. This analysis shows how Mark’s ritual narrations are conducive to evoking the audience’s experience of baptism, familiar to audience members as described in the undisputed Pauline epistles, the only descriptions of the rite that clearly antedate the composition of Mark. Publicly reading these narrated rituals creates an audience experience that neither requires the performance of the ritual in the context of the reading event nor an “acting out” of the ritual depicted in the narrative to create a participatory, communal experience of the text.